تكنولوجيا الاتصال الحديثة ودورها في جودة التعليم في المدرسة وخدمة المجتمع - ذيب, محمد; ضيف, الازهر (جامعة الوادي - University of Eloued, 2022)
تعد المدرسة من أهم مؤسسات التنشئة الاجتماعية في المجتمع، وهي حلقة الوصل بين الفرد وبيئته التفاعلية من خلال تقديم خدمات عديدة منها التربية والتعليم الذي يعد محور تطور المجتمعات ورقيّها، وبما أننا في عالم التطور والتقدم التكنولوجي وزمن العولمة . تعد وسائل تكنولوجيا الاتصال الحديثة من أهم مميزات العولمة التي دخلت على المدرسة وطرأت عدة تغيرات على التعليم وجودته وعلى المعلم والمتعلم في حد ذاته، فهذه الوسائل إما أن تكون لها فائدة على العناصر التعليمية الثلاثة وعلى المجتمع وإما إن تكون سلبية من خلال عدم حسن استغلال هذه الأخيرة وهنا تكمن إشكالية الورقة البحثية. The school is one of the most important institutions of social upbringing in society, and it is the link between the individual and his interactive environment by providing many services, including education, which is the focus of the development and progress of societies, and since we are in the world of development and technological progress and the time of globalization . where modern communication technology is one of the most important features Globalization that has entered the school and several changes have occurred in education and its quality and on the teacher and the learner as such. These means either have a benefit on the three educational elements and on society, or they are negative through the lack of good exploitation of the latter and here lies a problem Research paper.
Modern communication technology and its role in the quality of education in school and community service
مقال
Keywords: مدرسة، تعليم الكتروني، تكنولوجيا اتصال حديثة، مجتمع; School, e-learning modern, communication technology, society